Personal Satellite Services Second International ICST Confernce, PSATS 2010, Rome, Italy, February 2010 Revised Selected Papers - Sithamparanathan, Kandeepan; Marchese, Mario; Ruggieri, Marina; Bisio, Igor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on Personal Satellite Services, PSATS 2010, held in Rome, Italy, Februray 2010. The conference included a keynote speech, 4 regular technical tracks and 4 special sessions consisting of 33 high-quality scientific papers. These cover various topics such as Satellite Communications: Coding and Modulations, Multimedia Integration, Satellite Network: Quality of Service and Architectures and Applications and Services, as well as Delay-Tolerant Networks, Quantum Satellite Communications, Access Quality Processing and Applications of Satellite Imagery.
Track 1 - Satellite Communications: Coding and Modulation -- Overview of PHY-Layer Design Challenges and Viable Solutions in W-Band Broadband Satellite Communications -- FM Discriminator for AIS Satellite Detection -- Simulation of a Feasible Galileo System Operating in L1 and E5 Bands -- Compensations of Nonlinear Effects of TWTA for Signal Super-Positioning Satellite Communication Systems -- Track 2 - Satellite Communications: Multimedia Integration -- Comparative Analysis of Image Compression Algorithms for Deep Space Communications Systems -- Ka-Band Satellite Consumer Triple-Play and Professional Video Services -- On the Consideration of an UMTS/S-UMTS Based GEO-MSS System Architecture Design -- Track 3 - Satellite Networks: Quality of Service and Architectures -- End-to-End QoS Evaluation of IP-Diffserv Network over LEO Satellite Constellation -- A Cross-Layer Approach to Dynamic Bandwidth Allocation in Satellite Networks -- End-to-End QoS Measurement over a DVB-RCS Satellite Network -- Track 4 - Satellite Networks: Applications and Services -- Towards an IP/GSE-Only Signalling Framework for DVB Transmission Systems -- No-Reference H.264/AVC Statistical Multiplexing for DVB-RCS -- The Interplanetary Network Node: Architecture and Preliminary Performance Evaluation -- WiFi Assisted GPS for Extended Location Services -- Hybrid Satellite-Optical Ring Network for Regional Blackspots in Australia$1 (Bs National Broadband Network -- Special Session 1 - Delay Tolerant Network -- Mitigating Denial of Service Attacks in Delay-and Disruption-Tolerant Networks -- Delay/Disruption Tolerant Network Architecture for Aircrafts Datalink on Scheduled Routes -- Access Control Framework for Delay/Disruption Tolerant Networks -- ID Based Cryptography and Anonymity in Delay/Disruption Tolerant Networks -- Virtualization Technologies for DTN Testbeds -- Special Session 2 - Quantum Satellite Communications -- On the Polarization Analysis of Optical Beams for Use in Quantum Communications between Earth and Space -- 100 MHz Amplitude and Polarization Modulated Optical Source for Free-Space Quantum Communications at 850 nm -- Novel Techniques for Information Reconciliation, Quantum Channel Probing and Link Design for Quantum Key Distribution -- Using Redundancy-Free Quantum Channels for Improving the Satellite Communication -- Efficient Long Range Communication by Quantum Injected Optical Parametric Amplification -- Special Session 3 - Access Quality Processing and Applications of Satellite Imagery -- Semi-automatic Objects Recognition Process Based on Fuzzy Logic -- GeoEye-1: Analysis of Radiometric and Geometric Capability -- Local Detection of Three-Dimensional Systematic Errors in Satellite DSMs: Case Studies of SRTM and ASTER in Lombardy -- Interactive Access and Processing of Multispectral Imagery: The User in the Loop -- Time Series Analysis of the Digital Elevation Model of Kuwait Derived from Synthetic Aperture Radar Interferometry -- Special Session 4 - Satellite Based Emergency Services -- Cooperative Strategies of Integrated Satellite/Terrestrial Systems for Emergencies -- Software Defined Radio Assisted Localization for Emergency Scenarios -- Hybrid System HAP-WiFi for Incident Area Network.s
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information systems; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Computers and Society; Information Systems Applications (incl.Internet).